Interference Mitigation in Cooperative SFBC-OFDM. (7th May 2008) - Sreedhar Sreedhar, D. D.; Chockalingam Chockalingam, A. A.
Abstract : We consider cooperative space-frequency block-coded OFDM (SFBC-OFDM) networks with amplify-and-forward (AF) and decode-and-forward (DF) protocols at the relays. In cooperative SFBC-OFDM networks that employ DF protocol, (i), intersymbol interference (ISI) occurs at the destination due to violation of the "quasistatic" assumption because of the frequency selectivity of the relay-to-destination channels, and (ii) intercarrier interference (ICI) occurs due to imperfect carrier synchronization between the relay nodes and the destination, both of which result in error-floors in the bit-error performance at the destination. We propose an interference cancellation algorithm for this system at the destination node, and show that the proposed algorithm effectively mitigates the ISI and ICI effects. In the case of AF protocol in cooperative networks (without SFBC-OFDM), in an earlier work, we have shown that full diversity can be achieved at the destination if phase compensation is carried out at the relays. In cooperative networks using SFBC-OFDM, however, this full-diversity attribute of the phase-compensated AF protocol is lost due to frequency selectivity and imperfect carrier synchronization on the relay-to-destination channels. We propose an interference cancellation algorithm at the destination which alleviates this loss in performance.